Measurement Of Information Technology Used and Communication of Farmers Group In Sub-district of Jatinangor, Sumedang District - Aldika Karisnoviandi; Roni Kastaman; Irfan Ardiansah (Journal of Industrial and Information Technology in Agriculture, 2017)
Information and communication technology (ICT) can improve productivity and reduce costs / expenses in the agricultural sector and rural development. Jatinangor is one of sub-district on Sumedang with the highest economic growth, where the agricultural sector ranks third in contributing the economy. The use of ICT for farmers in Jatinangor it was not known the degree to which capable of being applied, then need to know the level of use of ICT by Jatinangor farmers. Method used in this research was descriptive method that described the data to determine size of the ICT usage level. Data is formulated into index numbers of ICT usage level or Information and Communication Technology Usage Level Quotient Index which was obtained by formulating an operational definition of variable using analysis of UNDP index calculation and Location Quotient analysis. The results of the study showed that the measurement of the ICT usage level covering by 4 indicators: farmers characteristic, farmers environment, ICT characteristic, and farmers behavior. Farmers group has the highest of the ICT use in Jatinangor is Harapan I, in Bina Karya Mandiri, Cileles Village with an index of 1,1380, and ICT absorption level of 50 %. Farmers group has the lowest of the ICT use is Jeruk Mipis, in Mulya Jaya, Cipacing Village with an index of 0,9156, and ICT absorption level of 36 %.